Does Acupuncture Benefit Delayed-Onset Muscle Soreness After Strenuous Exercise? A Systematic Review and Meta-Analysis - Huang, Chunwei; Wang, Zhipeng; Xu, Xiaoling; Hu, Shuangshuang; Zhu, Rong; Chen, Xi (Frontiers in Physiology, 2020)
Purpose: This systematic review and meta-analysis was designed to evaluate the effects of acupuncture intervention on alleviating delayed onset of muscle soreness (DOMS) after intense exercise. Method: Randomized controlled trials (RCTs) were searched from online databases including Medline (PubMed), Cochrane Library, Web of Science, Embase, PsycINFO, China Knowledge Resource Integrated Database (CNKI) and Wanfang (Chinese) up to April 2019. Data points were extracted from the eligible RCTs at the time points of 24h, 48h and 72h post strenuous exercise-induced DOMS, respectively. The outcomes of muscle soreness rating (MSR), Creatine Kinase (CK) and maximal isometric force (MIF) were pooled into the meta-analysis to assess the acupuncture intervention on DOMS. Results: Six eligible RCTs were included the meta-analysis and the results showed that acupuncture intervention significantly decreased MSR (SMD -0.49, 95%CI -0.73 to -0.24, P<0.001, I2=34%) and the serum level of CK (SMD -0.91, 95%CI -1.27 to -0.56, P<0.001, I2=30%), companied with improvement of the muscle strength ((MIF) (SMD 0.54, 95%CI 0.16 to 0.93, P=0.006, I2=51%)) after intense exercise. At the same time, the findings also revealed that acupuncture intervention had a long-lasting effect and tended to accumulate the effect size, the most efficacy on alleviating DOMS was at the time point of 72h post exercise. Conclusion: The current evidence indicates that acupuncture intervention after intense exercise could be effective for alleviating DOMS and improving the of muscle recovery.. The long-lasting effect of acupuncture intervention on DOMS started from 24h and would accumulate peak on 72h post exercise.